Auditoría de gestión para fortalecer el control administrativo del Registro Civil, identificación y cedulación del Carchi Agencia Tulcán. - González Benavides, Wilman Enríque (2015)
In the Civil Registry and Identification of Carchi Tulcán agency have been presented limitations marked on the efficiency, effectiveness and quality of processes aimed at user satisfaction in different areas. The management audit can be have control and value in a right way the appropriate and efficient use of resources with the proper handling of administrative processes, ensuring transparency of the services of the Civil Registry, Identification and Certification Agency of Carchi This research is based on a mixed mode, as the quantitative and qualitative paradigm is applied, the types of research used is applied research, field research, literature review, descriptive, correlational research also taken into account different methods both empirical and theoretical research techniques used is the survey which will be used in order to obtain the necessary information. and get an understanding of the research object, the instrument used is the questionnaire listing the questions that makes the staff the institution, the research is auditing. The result of this research is the audit report, the same which is composed of the findings, conclusions and recommendations to the different arcas involved.